Assessment of hand hygiene knowledge among medical and nursing students of Mysore medical college and research institute, Mysore - K., Manasa; S. G., Chandrakumar; B., Prashantha (International Journal Of Community Medicine And Public Health, 2018)
Background: Improper hand hygiene among health care workers is the main cause for many nosocomial infections. Lack of knowledge and lack of recognition of hand hygiene opportunities during patient care are mainly responsible for poor hand hygiene among health care workers. Methods: Knowledge on hand hygiene was assessed using WHO hand hygiene questionnaire among medical and nursing students of Mysore medical college and research institute. Results: Among 276 medical and 225 nursing students who participated in the study, 26% of medical and 33% of nursing students had received formal training in hand hygiene in the last three years. Less than 50% of students had knowledge on source, routes of transmission of germs and minimal time needed for hand rubbing in hospital setting. Conclusions: The knowledge is limited on hand hygiene actions which shows the importance of inclusion of hand hygiene topic in curriculum.